DAYA TAHAN ENAM JENIS KAYU ASAL PAPUA TERHADAP JAMUR PERUSAK - Sihati Suprapti; Djarwanto; Andianto (BRIN Publishing, 2016)
The resistance of six wood species against eight strains of destroying fungi was studied. Six wood species of ketapang (Terminalia complanata K. Sch.), pala hutan (Gymnacranthera paniculata Warb.), bipa (Pterygota horsfieldii (R.Br.) Kosterm.), kelumpang (Sterculia shillinglawii), manggis (Pentaphalangium parviflorum) and lancat (Mastixiodendron pachyclados Melch.), wereobserved using Kolle-flask methods. Wood samplesof inner and outer parts of the log were prepared from each species. Results show that M. pachyclados is classified as resistant (class II), P. horsfieldii is moderately resistant (class III), while the other four species are not-resistant (class IV) against destroying fungi. The average weight loss of the inner part is lower than that of the outer part logs, then both groups are classified as not-resistant wood (class IV). The lowest decay resistance is obtained from outer part of G. paniculata exposed to Pycnoporus sanguineus, while the highest decay resistance is taken from outer part of M. pachyclados exposed to Tyromyces palustris. The fungal ability to decay wood from the highest to the lowest are P. sanguineus, Polyporus arcularius, Polyporus sp., T. palustris, Schizophyllum commune, Lentinus lepideus, Phlebia brevispora, Chaetomiumglobosum, respectively.